Intra-Arterial Thrombolysis for Acute Stroke in Patients 80 and Older: A Comparison of Results in Patients Younger than 80 Years - Kim, D.; Ford, G.A.; Kidwell, C.S.; Starkman, S.; Vinuela, F.; Duckwiler, G.R.; Jahan, R.; Saver, J.L. (American Journal of Neuroradiology, 2007)
BACKGROUND AND PURPOSE: Intra-arterial fibrinolytic therapy is a promising treatment for acute ischemic stroke. Few data are available on its use in elderly patients. The purpose of this study was to compare the baseline characteristics, complications, and outcomes between intra-arterially treated ischemic stroke patients aged ≥80 years and their younger counterparts.METHODS: Patients aged ≥80 years (n = 33) were compared retrospectively with contemporaneous patients aged <80 years (n = 81) from a registry of consecutive patients treated with intra-arterial thrombolysis over a 9-year period.RESULTS: The very elderly and younger cohorts were very similar in baseline characteristics, including pretreatment stroke severity (National Institutes of Health Stroke Scale [NIHSS] 17 versus 16), differing only in history of stroke ransient ischemic attack (42% versus 22%, P = .01) and weight (66.8 versus 75.8 kg; P = .02). Significant differences in recanalization (TIMI 2–3) rates could not be detected between the very elderly and younger patients (79% versus 68%, P = .10). Rates of major symptomatic hemorrhage (7% versus 8%) and any intracerebral hemorrhage (39% versus 37%) did not differ. Outcomes at 90 days showed lower rates of excellent functional outcome (mRS ≤1, 26% versus 40%, P = .02) and survival (57% versus 80%, P = .01) among the very elderly.CONCLUSIONS: Intra-arterial fibrinolysis in the elderly can be accomplished with recanalization rates and hemorrhage rates equal to that in younger patients. Although mortality rates are higher and good functional outcomes are lower than in younger persons, nondisabling outcomes may be achieved in a quarter of patients. These findings suggest that the investigation and use of intra-arterial thrombolytic treatment in very elderly patients should not be avoided but pursued judiciously.